Late Mediaeval and Modern Era Glass Bottles from the Archaeological Museum of Istria (Archaeologia Adriatica, 2017)
The paper focuses on a small number of glass bottles kept at the Archaeological Museum of Istria. It includes mostly tableware, although a few small bottles may have been used in pharmacies or drugstores.
Keywords: Late Middle Ages; Modern Age; glass bottles; Archaeological Museum of Istria